DETERMINATION OF ENERGY CONSUMPTION CHANGES AND DISTRIBUTION IN COMPONENTS OF AN IMPROVED COTTON REGENERATOR DEVICE USING ELECTRONIC SENSORS (Web of Technology: Multidimensional Research Journal, 2025)
This article investigates the performance of newly designed working elements in a regenerator device used to separate residual cotton fibers (linters) from waste generated during raw cotton cleaning at ginneries. The study focuses on changes in energy consumption and its distribution within the device, which were measured using electronic sensors and oscillographic analysis. Experimental results show the effects of comb geometry on airflow dynamics and energy efficiency, highlighting the potential for improved fiber recovery and reduced energy loss.